0942 Treatment Effects Of Imagery Rehearsal Therapy In Female Nightmare Disorder Patients With Trauma History: Data driven Analyses Using Resting State Functional Connectivity Study. (27th April 2018) - Suh, S; Kim, J; Han, S; Cho, N; Chang, J; Woo, D; Choi, S; Joo, E
Abstract: Introduction: Imagery Rehearsal Therapy(IRT) is relatively a new evidence-based treatment for nightmare disorder patients. This is the first time investigating the treatment effects of IRT using fMRI. Based on past studies by Shen et al.(2016), nightmare disorder patients show increased regional homogeneity in both the anterior cingulate and inferior parietal lobule. This study used a one group pre-post design to investigate the effects of IRT in Korean nightmare disorder patients with trauma exposure in sleep, mood, and neurocognitive domains. Methods: 12female nightmare disorder patients with trauma history(mean age28.92 ± 8.49) were selected through a semi-structured interview based on the DSM-5 criteria for nightmare disorder. All patients received 5 weekly sessions of IRT, with attrition rate being 33%(n=4). They completed the following questionnaires before and after IRT: Insomnia Severity Index, Disturbing Dream and Nightmare Severity Index, Beck Depression Inventory, PTSD Checklist for DSM-5, and Depression Symptom Inventory-Suicidality Subscale. Neuroimaging data was also collected pre-and post-treatment using fMRI(3Tesla). FMRI data were band-pass filtered(0.009–0.08 Hz), spatially smoothed(5-mm FWHM), and several sources of spurious variance were removed(6 head motion, signal from CSF, and signal from WM). To compute functional connectivity(fc) matrix, the mean time courses of fMRI signal were extracted for each ROI, based on the Automated Anatomical Labeling(AAL) brain atlas(left:45ROIs, right:45ROIs), and Pearson's correlation coefficients were computed between ROIs, resulting in 90x90 correlation matrices. Results: After IRT, participants showed significant decrease in insomnia symptoms, nightmares, depression and post-traumatic stress disorder( ps ≤.016), with a 29% decrease in total nightmares per week after treatment. Compared with pre-treatment, patients showed a decrease in abnormally heightened connectivity between the anterior cingulate and the following areas: medial/orbitofrontal cortex and inferior and superior parietal areas. Conclusion: Our results support previous evidence of the treatment effects of IRT on sleep and mood. Furthermore, IRT appears to reduce heightened connectivity between the anterior cingulate and frontal and parietal areas. Support (If Any): This work was supported by the Ministry of Education of the Republic of Korea and the National Research Foundation of Korea.(NRF-2016S1A5B6914283).